Study on flow characteristics of natural gas containing CO2 invading wellbore during drilling - He, Haikang; Sun, Baojiang; Sun, Xiaohui; Li, Xuefeng; Shan, Zhengfeng (Frontiers in Physics, 2022)
The dissolution of invaded gas in the drilling fluid during drilling results in an increase in the gas invasion concealment. This is of great significance for the development of acid gas reservoirs to determine the solubility change and multiphase flow law in an annulus after invasion by natural gas with high CO2 content. In this study, control equations of gas–liquid flow during drilling gas invasion are established considering the influence of gas solubility. For the prediction of gas solubility, the interaction parameters of CH4 and water in the Peng–Robinson equation of state are optimised to establish a gas solubility prediction model. The solubility of natural gas with high CO2 content in water and brine solution is measured through phase-equilibrium experiments. The results indicate that the newly optimised solubility model can accurately predict the solubility of CH4 and CO2 in water, and the prediction error is within 5%. Moreover, the prediction error for the solubility of CH4 and CO2 mixed gas is within 15%. The analysis of gas invasion in example engineering drilling applications reveals that an increase in the CO2 content in the invaded gas leads to a slow change in the mud-pit increment, and the concealment strengthens as the distance between the gas-migration front and the wellhead increases. Gas solubility has a significant impact on the monitoring of gas invasion in low permeability reservoirs.